Factors Related to Instructional Leadership Perception and Effect of Instructional Leadership on Organizational Variables: A Meta-Analysis - Şişman, Mehmet (EDAM, 2016)
In this meta-analysis, effects of teacher characteristics on instructional leadership perceptions and some organizational variables is tested. Findings of the total of 67 independent studies are gathered in the metaanalysis which represents a population of 36,756. According to the findings of this meta-analysis performed by using random effects model; while task type, school level and type have effect on instructional leadership perception, gender and branch of the teachers have no effect. Besides, it is discovered in this meta-analysis that instructional leadership has medium-level effect on some organizational variables. According to the analysis results, the most reliable scale for measuring instructional leadership is found to be ‘Instructional Leadership Behaviors of School Administrators’ scale developed by Şişman.
Keywords: Instructional Leadership; Organizational Variable; Meta-Analysis; Standardized Mean Difference